Prevention of Skin Damage Using Disposable Retractors in Open Hepatobiliary Surgery - Hafiz Aamir Bashir, Waqas Hussain Qureshi, Nasir Naseem Akhtar, Muhammad Zafar, Sirajuddin, Sadaffasih, Muhammad Abid Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Hepatobiliary surgeries, which encompass a wide range of complex procedures such as liver resections, gallbladder surgeries, and bile duct interventions, present significant challenges due to the delicate nature of the organs involved and the intricacies of the surgical techniques. Objective: To assess the impact of disposable retractors on the incidence, severity, and outcomes of skin damage in patients undergoing open hepatobiliary surgery. Methods: A retrospective observational study was conducted at Pir Abdul Qadir Shah Jeelani Institute of Medical Sciences Gambat, Sindh during May 2022 to December 2022. A total of 155 patients scheduled for open hepatobiliary surgery. Patients were randomly assigned to either the intervention group (disposable retractors, n=78) or the control group (traditional metal retractors, n=77). The primary outcome was the incidence of skin damage, including abrasions, ischemia, and pressure sores. Secondary outcomes included the severity of skin damage, time to wound healing, post-operative pain levels, and patient satisfaction. Results: The incidence of skin damage was significantly lower in the intervention group (10.3%) compared to the control group (27.3%) (p = 0.02). The severity of skin damage, as measured by the PUSH score, was also significantly lower in the intervention group (mean score = 1.2) versus the control group (mean score = 3.5) (p = 0.03). The intervention group demonstrated a delayed onset of skin damage (mean = 3.5 days) compared to the control group (mean = 2.1 days) (p = 0.01). Additionally, the intervention group had a faster time to wound closure (12.4 ± 2.1 days vs. 16.3 ± 3.4 days, p = 0.03) and reported lower post-operative pain levels and higher patient satisfaction (mean score = 9.1 vs. 7.5, p = 0.01). Conclusions: It is concluded that disposable retractors significantly reduce the incidence and severity of skin damage in open hepatobiliary surgery. The use of disposable retractors also results in faster wound healing, lower pain levels, and improved patient satisfaction. Keywords: Hepatobilliary Surgery, Skin Damage, Severity, Disposable Retractors.